The Impact of using Marzano Model on Academic and Motivation Achievement for the Sixth Grade in Science and their Attitudes Towards it - Abdel-Salam Muqbel Mashal (My University, 2014)
This study aimed to explore the impact of using Marzano Model on Academic and Motivation Achievement of the Sixth Grade in Science and their Attitudes Towards it in public schools in Tulkarm Directorate during the first semester ( 2013/ 2014). This was done by answering the main question : what is the Impact of using Marzano Model on Academic and Motivation Achievement for the Sixth Grade in Science and their Attitudes Towards it in Tulkarm District? In order to answer the question and test their assumptions, the study was carried out on a sample of (52) male students of the sixth for Boys' was intentionally chosen. To achieve the aims of the study :on a male school ¬¬– two sections in school was carried out. The two sections were distributed randomly in school. One of them was experimental consisting of a male section whose members rose to (26) male students and the other was controlled consisting of a male section whose members rose to (26) male students. The section of experimental group studied the unit (Motion and Force ) in science subject matter using an educational program based on "Marzano Model" prepared by the researcher. The validity and reliability of the program were examined. while the section of the controlled group studied the same unit in regular method. The researcher carried out achievement – test which consisted of (30) test items of multiple-choice question type. The reliability of the test was checked by arbitrators. Its validity factor was calculated by using kuder Richardson formula (20). The researcher used a measurement for achievement motivation of )69( test items The reliability of the test was checked by arbitrators. Its validity factor was calculated by using Cronbach's Alpha formula whose value rose to 0.86. and a measurement for the attitudes towards science consisted of (25) statements: (13) statements were positive and (12) statements were negative. The reliability of the the measurement was checked by arbitrators. Its validity factor was calculated by using Cronbach's Alpha formula, whose value rose to 0.88. Also the difficulty and discrimination parameters of achievement – test was calculated. The data was analyzed by using Analysis of Covariance (ANCOVA); the statistical analysis showed these results on the significance level (α = 0.05): 1. There is a difference which has a statistical significance between the averages of students' achievement of the experimental group and the controlled group which is due to the teaching method, and for Marzano model. 2. There is a difference which has a statistical significance between the averages of students motivation achievement of the experimental group and the controlled group which is due to the teaching method, and for Marzano model. 3. There is a difference which has a statistical significance between the averages of students' attitudes towards science of the experimental group and the controlled group which is due to the teaching method, and for Marzano model; According to the findings the researcher adopting anew methods in teaching, such as Marzano model because of it increases Achievement, motivation and attitudes towards science.

هدفت هذه الدراسة إلى استقصاء أثر استخدام نموذج مارزانو لأبعاد التعلم في التحصيل ودافع الإنجاز لدى طلاب الصف السادس في مادة العلوم واتجاهاتهم نحوها في المدارس الحكومية في محافظة طولكرم في الفصل الدراسي الأول (2013/2014 م)، وذلك من خلال الإجابة عن السؤال الرئيس التالي: ما أثر استخدام نموذج "مارزانو" لأبعاد التعلم في التحصيل ودافع الإنجاز لدى طلاب الصف السادس في العلوم واتجاهاتهم نحوها في محافظة طولكرم ؟ وللإجابة عن سؤال الدراسة واختبار فرضياته، استخدم الباحث المنهج شبه التجريبي، تم تطبيق الدراسة على عينة الدراسة المؤلفة من (52) طالباً من طلاب الصف السادس الأساسي، إذ تمّ اختيار المدرسة بطريقة قصدية لتحقيق أهداف الدراسة بواقع شعبتين، وزعت الشعبتان عشوائياً إلى مجموعتين، واحدة تجريبية مكونة من شعبة ذكور بلغ عدد أفرادها (26) طالباً، والأخرى ضابطة مكونة من شعبة ذكور بلغ عدد أفرادها 26)) طالباً، وقد درست شعبة المجموعة التجريبية وحدة الحركة والقوة من منهاج العلوم باستخدام برنامج تعليمي وفق نموذج مارزانو من إعداد الباحث، تمّ التأكد من صدقه وثباته، بينما درست الشعبة في المجموعة الضابطة نفس الوحدة بالطريقة الاعتيادية. استخدم الباحث اختباراً تحصيلياً مكوناً من (30) فقرة من الاختيار من متعدد، تمّ التأكد من صدقه بالمحكمين، وحساب معامل ثباته باستخدام معادلة ريتشاردسون (20)، وقد بلغت قيمته 0.93)) واستخدم أيضاً مقياساً لدافع الإنجاز, تمّ التأكد من صدقه بالمحكمين، وحساب معامل ثباته باستخدام معادلة كرونباخ ألفا، وقد بلغت قيمته (0.86)، كما استخدم أيضاً مقياساً للاتجاهات نحو العلوم مكوناً من (25) عبارة، منها (13) عبارة موجبة و(12) عبارات سالبة، تمّ التأكد من صدقه بالمحكمين، وحساب معامل ثباته باستخدام معادلة كرونباخ ألفا، وقد بلغت قيمته (0.88). حللت البيانات باستخدام تحليل التباين الأحادي المشترك (ANCOVA)، وقد أظهرت التحليلات الإحصائية النتائج الآتية عند مستوى الدلالة:(0.05 = α). -1 يوجد فرق ذو دلالة إحصائية بين متوسطي علامات طلاب المجموعة التجريبي والمجموعة الضابطة في الاختبار التحصيلي، يعزى إلى طريقة التدريس. -2 يوجد فرق ذو دلالة إحصائية بين متوسطي علامات طلاب المجموعة التجريبي والمجموعة الضابطة على مقياس دافعية الانجاز، يعزى إلى طريقة التدريس. -3 يوجد فرق ذو دلالة إحصائية بين متوسطي علامات طلاب المجموعة التجريبية والمجموعة الضابطة على مقياس الاتجاهات، يعزى إلى طريقة التدريس. وفي ضوء النتائج التي توصل إليها الباحث خرجت الدراسة بمجموعة من التوصيات والمقترحات منها ضرورة استخدام نموذج مارزانو لأبعاد التعلم في التدريس لدوره الايجابي في زيادة تحصيل الطلبة وإثارة دافعيتهم فضلاً عن نمو اتجاهاتهم الايجابية نحو العلوم، كذلك قيام الإدارة العامة للمناهج بأخذ نتائج الدراسة بعين الاعتبار عند إعداد مناهج العلوم والمواد التعليمية.
أثر استخدام نموذج "مارزانو" لأبعاد التعلم في التحصيل ودافع الإنجاز لدى طلاب الصف السادس في العلوم واتجاهاتهم نحوها